The Effect of Service Quality, Marketing Mix, Customer Satisfaction, and Customer Trust on Customer Loyalty at Buley Steak - Adiputra, Henry Jonathan; Hartoyo, Hartoyo; Yuliati, Lilik Noor (Dinasti Publisher, 2025)
This study aims to examine perceptions and analyze the effect of service quality and marketing mix on customer satisfaction, trust, and loyalty toward Buley Steak. A quantitative research method was applied through a survey conducted with end customers who have consumed Buley Steak products for at least in the past year. A total of 280 respondents completed the questionnaire distributed online. The independent variables in this study are service quality and marketing mix, while the dependent variables include satisfaction, trust, and customer loyalty. Data were analyzed using descriptive statistical techniques. The findings reveal that service quality significantly affects both customer satisfaction and trust. Similarly, the marketing mix also has a significant impact on satisfaction and trust. Furthermore, customer satisfaction strengthens trust, which in turn significantly affects loyalty. Based on these findings, managerial implications suggest that Buley Steak should enhance service quality and marketing strategies to foster customer satisfaction, build trust, and achieve long-term customer loyalty.